Enhancing Permanence for Vocabulary Learning on 2nd Grade Students in Turkey Through Music (GIST – Education and Learning Research Journal, 2021)
Music plays an important role in students' language development. Because the process of acquiring and developing language skills of the individual and the process of learning to make music work have many similarities. In this study, the effect of teaching word with music with the normal intelligence and development level of 2nd grade students on the learning of the meaning of the word and ensuring the permanence of the word has been examined. Quasi-experimental design with experimental control group was used in the study. The research was carried out with 43 second grade students and the data were analyzed with ANOVA test. According to the results of the study, it is concluded that the teaching of vocabulary with music both the meaning of the word and providing the persistence of learning was found to be useful.
Keywords: Music; Vocabulary teaching; Learning the meaning of the word; Persistance; elementary grades; mother tongue